Study effect plant extract for synthesis of Graphene Oxide NPs (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Graphene oxide nanoparticles (GONPs) have been widely used in medical applications because they are inexpensive, safe and effective. This research successfully produced GONPs preparation of mixing the plant extract (garlic) with graphene solution at 300 °C for 2 hours by chemical method. GONPs prepared by using the plant extract (garlic) were characterization by X-ray diffraction (XRD), Ultravilote visible (UV-visible) Spectrum, and fourier transform infrared (FT-IR) spectrum. The small crystalline size (8.3 to 23 nm), and (hexagonal) structure, UV-visible spectrum shows for the optical band gap value from (3.36) eV to GONPs NPs using garlic extract. FT-IR spectrum show the absorpption band strong is 717 cm-1 of GONPs using garlic extract.